Character Education: Strengthening the Character of Elementary School Students based on Wayang Sukuraga through Practice of Noble Morals - Atot Sugiri (Institut Agama Islam Ma'arif NU (IAIMNU) Metro Lampung, 2023)
This study is to learn about character education based on local wisdom, Wayang Sukuraga, through the cultivation of noble morality in primary school. The approach used in this study is a qualitative approach with a qualitative descriptive method aimed at knowing the picture of character education on the basis of Wayang Sukuraga by cultivating the noble morals of students in elementary schools. Data collection was carried out with interview techniques, observations, and documentation studies. As for the results of this study, the strengthening of character education based on the phenomenon of Sukuraga through the cultivation of the noble morality of students in the school is very supportive both in student activities and school programs. This can be seen from the values contained in philanthropy, which support the formation of true human character. Because the philosophy is taken from the stories of everyday human life, Thus, the strengthening of character education based on this philosophy can be implemented by students in the practice of noble morals in school and outside school. This can be demonstrated by the vision, mission, and purpose of the school; character education strengthening programs with the integration of learning processes implemented in everyday life, integrated implementation in the intrakuricular, non-curricular, as well as extracurricular strategies of character strengthening education using methods of cultivation, uniformity, spontaneous activities, and student character successes that are more diligent in devotion. Keywords: Character Education, Wayang Sukuraga, Elementary Schools, Noble Morals